Invasive mucinous adenocarcinoma of the lung - Xu, Lu; Li, Chenghui; Lu, Hongyang (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Invasive mucinous adenocarcinoma (IMA) is a unique histological subtype of adenocarcinoma. Due to its low incidence rates, survival data for IMA is scarce and often contradictory. The clinical manifestations of IMA are not precise as compared to other adenocarcinomas, with some patients having bronchial mucus overflow. Difference in immunohistochemical expression levels is present in IMA and invasive non-mucinous adenocarcinomas (INMA). Kirsten rat sarcoma viral oncogene homolog (KRAS) mutations are more frequent in IMAs, while epidermal growth factor receptor (EGFR) mutations are relatively rare. This makes it distinct from the other more common adenocarcinomas. Neuregulin 1 (NRG1) gene fusions are considered important therapeutic targets for IMA, suggesting that Afatinib may be an effective drug to treat IMA. However, IMA prognosis remains controversial.